Effect of Saccharomyces boulardii in dogs with chronic enteropathies: double‐blinded, placebo‐controlled study. (3rd March 2018) - D'Angelo, Simona; Fracassi, Federico; Bresciani, Francesca; Galuppi, Roberta; Diana, Alessia; Linta, Nikolina; Bettini, Giuliano; Morini, Maria; Pietra, Marco
Abstract : Saccharomyces boulardii is used to treat acute and chronic enteropathies in humans, but to date, no studies have evaluated the use of this yeast in dogs. The current study, a prospective non‐randomised, double‐blinded, placebo‐controlled study, evaluated the effects of S boulardii in healthy dogs and dogs with chronic enteropathies (CE). Four healthy dogs and 20 dogs with CE were included. In healthy dogs, S boulardii was administered for 10 days. Possible short‐term adverse effects were recorded, and quantitative stool cultures for yeasts were performed. In dogs with CE, S boulardii or a placebo was administered in addition to standard treatment protocols. Canine Chronic Enteropathy Clinical Activity Index, abdominal ultrasonography, gastroenteroscopy and histology were performed at the time of diagnosis and after 60 days of treatment. In healthy dogs, S boulardii reached a steady state in five days and was completely eliminated on day 4 after administration. No short‐term side effects were seen. Clinical activity index, stool frequency, stool consistency and body condition score improved significantly in dogs with CE receiving S boulardii versus the placebo. In conclusion, S boulardii can be safely used in dogs with CE and seems to achieve better control of clinical signs than standard therapy alone.